Chapter Professional choices and personal values: Similarities and differences between Schein's career anchors and Schwartz basic values - Arra, Aldo (Proceedings e report, 2023)
Consistency between personal values and career choices is essential to achieve job satisfaction and to attain positive career outcomes and self-realization. Schwartz and Bilsky (1987) propose ten basic values, measured through the Portrait Value Questionnaire, related to the universal needs of existence: self-direction, stimulation, hedonism, power, achievement, security, conformity, tradition, universalism, and benevolence. These values are organized in a circular shape, according to their similarities and dissimilarities and following the contraposition between openness to change and conservation, and between self-enhancement and self-transcendence. Focusing on professional goals and aspirations, Schein's Career Orientation Inventory (1990) identifies eight anchors that drive employees' career paths and orientations: general managerial competence, technical/functional competence, autonomy/independence, security/stability, entrepreneurial creativity, dedication to a cause, pure challenge, life-style. Schein affirms that a career anchor is "that one element in a person self-concept, which he or she will not give up even in the face of difficult choices" (1990). In this paper, we aim at understanding the mutual relationship between the paradigms proposed by Schwartz and Schein, in order to enlighten how personal motivations inform career preferences and choices. We administered the Portrait Value Questionnaire and the Career Orientation Inventory scales to a sample of 253 respondents who work in different fields and positions, through a survey questionnaire. Results show a high level of consistency between Schwartz's and Schein's theoretical frames. Those who are more oriented to the openness to change dimension tend to favour careers of autonomy and entrepreneurial creativity, while a conservative motivation leads to more safe and stable careers; analogously, personal values of self-enhancement support challenging careers while self-transcendence pushes for dedication to a cause and work-life balance.